Pendidikan Sebagai Katalisator Demokrasi: Studi Kasus Partisipasi Politik Perempuan Di Kuba - Swandita Mahayasa, Dias Pabyantara; Salsabila, Ismayrenna Dwi (Review of International Relations, 2024)
Improving the quality of education in Cuba encourages the achievement of gender equality, especially in increasing the quota of women in the Cuban government. The revolution of the education system achieved through collaboration between the government and civil society is able to ignite the awareness of women of their rights in political participation. Comprehensive commitment and implementation in Cuba produces a high quality education index and makes Cuba one of the countries with the best education system in the world. The existence of an educational correlation and the achievement of gender -friendly politics is shown by the stable quota of women in the Cuban parliament. By looking at the system, quality and quantity of education as well as government and civil society programs in achieving gender equality and women's empowerment, this research found that there is a relationship between the equality of education as the focus of the construction of the Cuba by achieving the stability of the distribution of seats in parliament through the gender inequality index, especially the value Stable on the quota of women's quota in the Cuban government. This is inseparable from the joint effort between the government and the civil society represented by a feminist organization in Cuba namely Federation of Cuban Women (FMC).